THE POWER OF IMAGES: THE BIBLE IN ART AND VISUAL REPRESENTATION IN SOUTH AFRICA - Cornelius, Izak (Scriptura, 2004)
Artists are not merely illustrators, but also interpreters of ancient texts such as the Bible. The works of South African artists such as Mbatha on biblical stories are well known, but the art of the Namibian Muafangejo should also be acknowledged. Examples from the book of Genesis in the medium of the linoprint are discussed and compared with other representations in art. The work of Mbatha and Muafangejo represent an African reading of the text.